Lymph Node-Targeting Nanovaccine through Antigen-CpG Self-Assembly Potentiates Cytotoxic T Cell Activation - Xiaobo Xi; Lijun Zhang; Guihong Lu; Xiaoyong Gao; Wei Wei; Guanghui Ma (Journal of Immunology Research)
Therapeutic vaccines that arouse the cytotoxic T cell immune response to reject infected cells have been investigated extensively for treating disease. Due to the large amounts of resident antigen-presenting cells (APCs) and T cells in lymph nodes, great efforts have been made to explore the strategy of targeting lymph nodes directly with nanovaccines to activate T cells. However, these nanovaccines still have several problems, such as a low loading efficiency and compromised activity of antigens and adjuvants derived from traditional complicated preparation. There are also safety concerns about materials synthesized without FDA approval. Herein, we construct an assembled nanoparticle composed of an antigen (ovalbumin, OVA) and adjuvant (CpG) to ensure its safety and high loading efficiency. The activity of both components was well preserved due to the mild self-assembly process. The small size, narrow distribution, negative charge, and good stability of the nanoparticle endow these nanovaccines with superior capacity for lymph node targeting. Correspondingly, the accumulation at lymph nodes can be improved by 10-fold. Subsequently, due to the sufficient APC internalization and maturation in lymph nodes, ~60% of T cells are stimulated to proliferate and over 70% of target cells are specifically killed. Based on the effective and quick cellular immune response, the assembled nanoparticles exhibit great potential as therapeutic vaccines.